Comparative study on satellite-based data communication techniques - Sujithra, T.; Nivedhitha, G.; Durai, S.; Suresh, A. (International Journal of Engineering and Technology, 2018)
Satellite communication is highly useful in collecting data from human unattended area, early warning of natural disasters, earth observation and so on. Numerous work has been carried out in the area of satellite based communication and networking. It is an inseparable component from the Global Network infrastructure. In this study, we recapitulate, compare and comments on proposed approaches for the satellite based communication with keeping in view the parameters such as efficient data transfer between the satellite and the ground station, various on-board data processing techniques, prioritizing the payload data, load balancing and optimizing energy consumption issues.